Travellers and their journeys: A dynamic conceptualisaton of transient migrants' and backpackers' behaviour and experiences on the road - Schapendonk, J.; van Liempt, I.; Spierings, B. (Oxford University Press, 2015)
In this article it is argued that ‘the journey’—as an embodied form of travel from oneplace to the other—is a fruitful analytical starting point to bring migration and tourismstudies in closer dialogue with each other. With our focus on the ‘en route’ behaviourand experiences of two prototypical mobile ﬁgures (the transient migrant and thebackpacker), we go beyond the usual categorical divisions of human mobility basedon temporality (temporary tourists vs. long-term migrants) and politicization (wel-comed tourists vs. unwanted migrants). With our empirical ﬁndings on migrants’ jour-neys and our analysis of published articles in tourism studies, we identify three aspects(personal transformation, social networking and risk taking) along which we concep-tually mirror and merge the embodied journeys of the prototypical travellers. Theanalysis identiﬁes relevant commonalities of different mobility processes andillustratesthat individuals on the move easily jump over the categorical divide of migrants/tour-ists across time and space. We ﬁnally use these insights to contribute further to amobility-driven research agenda in migration studies.
Keywords: journey; migration; tourism; personal transformation; social networking; risk taking; Taverne